Invasively Measured Aortic Systolic Blood Pressure and Office Systolic Blood Pressure in Cardiovascular Risk Assessment: A Prospective Cohort Study. Issue 3 (September 2016) - Laugesen, Esben; Knudsen, Søren T.; Hansen, Klavs W.; Rossen, Niklas B.; Jensen, Lisette Okkels; Hansen, Michael G.; Munkholm, Henrik; Thomsen, Kristian K.; Søndergaard, Hanne; Bøttcher, Morten; Raungaard, Bent; Madsen, Morten; et al.
Abstract : Aortic systolic blood pressure (BP) represents the hemodynamic cardiac and cerebral burden more directly than office systolic BP. Whether invasively measured aortic systolic BP confers additional prognostic value beyond office BP remains debated. In this study, office systolic BP and invasively measured aortic systolic BP were recorded in 21 908 patients (mean age: 63 years; 58% men; 14% with diabetes mellitus) with stable angina pectoris undergoing elective coronary angiography during January 2001 to December 2012. Multivariate Cox models were used to assess the association with incident myocardial infarction, stroke, and death. Discrimination and reclassification were assessed using Harrell's C and the Continuous Net Reclassification Index. Data were analyzed with and without stratification by diabetes mellitus status. During a median follow-up period of 3.7 years (range: 0.1–10.8 years), 422 strokes, 511 myocardial infarctions, and 1530 deaths occurred. Both office and aortic systolic BP were associated with stroke in patients with diabetes mellitus (hazard ratio per 10 mm Hg, 1.18 [95% confidence interval, 1.07–1.30] and 1.14 [95% confidence interval, 1.05–1.24], respectively) and with myocardial infarction in patients without diabetes mellitus (hazard ratio, 1.07 [95% confidence interval, 1.02–1.12] and 1.05 [95% confidence interval, 1.01–1.10], respectively). In models including both BP measurements, aortic BP lost statistical significance and aortic BP did not confer improvement in either C-statistics or net reclassification analysis. In conclusion, invasively measured aortic systolic BP does not add prognostic information about cardiovascular outcomes and all-cause mortality compared with office BP in patients with stable angina pectoris, either with or without diabetes mellitus. Abstract : Supplemental Digital Content is available in the text.